2003
DOI: 10.1073/pnas.0736600100
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific contributions to the pH dependence of protein stability

Abstract: Understanding protein stability is a significant challenge requiring characterization of interactions within both folded and unfolded states. Of these, electrostatic interactions influence ionization equilibria of acidic and basic groups and diversify their pK a values. The pH dependence of the thermodynamic stability (⌬G FU) of a protein arises as a consequence of differential pK a values between folded and unfolded states. Previous attempts to calculate pHdependent contributions to stability have been limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
130
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(132 citation statements)
references
References 37 publications
2
130
0
Order By: Relevance
“…Furthermore they demonstrated that the non-native interactions persisted in the transition state for folding [18,31]. DSE effects involving charged residues have also been detected in the drkN SH3 domain [16], although they are believed to be due interactions involving adjacent residues. Work on T4 lysozyme, RNase A and RNase T1 have shown that mutations that are predicted to increase protein stability by altering native state electrostatic interactions often have much smaller effects than expected.…”
Section: Electrostatic Interactions Are Found In the Denatured State mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore they demonstrated that the non-native interactions persisted in the transition state for folding [18,31]. DSE effects involving charged residues have also been detected in the drkN SH3 domain [16], although they are believed to be due interactions involving adjacent residues. Work on T4 lysozyme, RNase A and RNase T1 have shown that mutations that are predicted to increase protein stability by altering native state electrostatic interactions often have much smaller effects than expected.…”
Section: Electrostatic Interactions Are Found In the Denatured State mentioning
confidence: 99%
“…However, indirect methods normally need to be used to study the DSE under native conditions [13]. A wide range of approaches have been used including, but not limited to, the study of peptide fragments, the analysis of destabilizing point mutants or truncation mutants, amide 1 H/ 2 H exchange experiments of the native state, changes in m-values upon mutation and the analysis of the pH dependence of protein stability [14][15][16][17]. Numerous investigations have provided compelling evidence for compact DSEs with significant amounts of residual structure under native conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, pK a values obtained directly from the D state are more accurate than those inferred from random coil model compounds 12,28,29,35 . To model the D state of GCN4p we studied the protein in 6 M urea, since this is often the endpoint of protein denaturation studies 13 .…”
Section: Pk a Values In The Denatured Statementioning
confidence: 99%
“…Most of these pKs do not differ significantly from the intrinsic pK values estimated earlier by Nozaki and Tanford. 2 It will be interesting to compare these values to the pKs determined in unfolded proteins. [3][4][5][6][7][8][9][10] Most of the pK values for folded proteins have been measured directly using techniques based on nuclear magnetic resonance (NMR). [11][12][13] A smaller number have been measured using indirect techniques.…”
Section: Introductionmentioning
confidence: 99%